Utility of Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Systemic Immune Inflammation Index as Prognostic, Predictive Biomarkers in Patients with Metastatic Renal Cell Carcinoma Treated with Nivolumab and Ipilimumab - Koji Iinuma (MDPI AG, 2021)
The aim of this study was to assess the utility of neutrophil-to-lymphocyte ratio (NLR), plate-let-to-lymphocyte ratio (PLR), and systemic immune inflammation index (SII) as predictive biomarkers with oncological outcomes for metastatic renal cell carcinoma (mRCC) patients treated with nivolumab and ipilimumab (NIVO + IPI). We conducted a retrospective multicenter cohort study assessing patients with mRCC treated with NIVO + IPI at eight institutions in Japan. In this study, the follow-up period was median 14 months. The 1-year overall- and progression-free survival (PFS) rates were 89.1% and 63.1, respectively. The objective response rate (ORR) and disease control rate (DCR) were 41.9% and 81.4%, respectively. The 1-year PFS rates were 85.7% and 49.1% for NLR ≤ 2.8 and >2.8, respectively (p = 0.005), and 75.5% and 49.7% for PLR ≤ 215.6 and >215.6, respectively (p = 0.034). Regarding SII, the 1-year PFS rates were 90.0% and 54.8% when SII was ≤561.7 and >561.7, respectively (p = 0.023). Therefore, NLR, PLR, and SII levels in mRCC patients treated with NIVO + IPI may be useful in predicting oncological outcomes.